2019
DOI: 10.1186/s12968-019-0545-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased extracellular volume in the liver of pediatric Fontan patients

Abstract: Background Patients with single ventricle physiology are at increased risk for developing liver fibrosis. Its extent and prevalence in children with bidirectional cavopulmonary connection (BCPC) and Fontan circulation are unclear. Extracellular volume fraction (ECV), derived from cardiovascular magnetic resonance (CMR) and T1 relaxometry, reflect fibrotic remodeling and/or congestion in the liver. The aim of this study was to investigate whether pediatric patients with single ventricle physiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 43 publications
3
8
0
Order By: Relevance
“…The elevated hepatic T1, extracellular volume fraction, and elastography values confirmed previous findings from retrospective MR studies in adults and children with Fontan [18,21,22] and studies on US and MR elastography after Fontan completion [19,20,27,28]. The advantage of our study was the representative, unselected, relatively large national cohort of adolescents with Fontan circulation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The elevated hepatic T1, extracellular volume fraction, and elastography values confirmed previous findings from retrospective MR studies in adults and children with Fontan [18,21,22] and studies on US and MR elastography after Fontan completion [19,20,27,28]. The advantage of our study was the representative, unselected, relatively large national cohort of adolescents with Fontan circulation.…”
Section: Discussionsupporting
confidence: 87%
“…US shear-wave elastography is simpler and less resource-demanding than MR, and is routinely used to assess adult chronic liver disease [16,17]. Few studies have employed hepatic MR T1 mapping or elastography to evaluate fibrosis or congestion in people with Fontan circulation [18][19][20][21][22]. We hypothesized that adolescents with Fontan circulation might display elevations in fibrosis markers, based on MR T1 mapping, extracellular volume fraction, and US shear-wave elastography.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, relaxometry of the liver in cardiac patients has received limited interest. Preliminary results suggested that mapping of the liver may be useful in patients with tetralogy of Fallot and in Fontan circulation [15,16]. Our ndings not only endorse those ndings but suggest a broader use of liver MR relaxometry offering valuable information in cardiac conditions which affect the liver with potential deleterious consequences, such as cardiac cirrhosis.…”
Section: Discussionsupporting
confidence: 69%
“…16,28,29 Alternatively, only a few studies have reported the evaluations of T 1 mapping for FALD in children and adolescents. 17,18 They demonstrated significantly elevated liver native T 1 values in Fontan patients than normal controls, and a strong correlation with MR elastography-derived liver stiffness. 17,18 However, whether T 1 mapping can differentiate congestion from fibrosis remains unclear.…”
Section: Fald and Liver Native T 1 Valuesmentioning
confidence: 87%
“…T 1 mapping is a novel MRI technology to quantify the diffuse damage/fibrosis/congestion/edema/inflammation of parenchyma in organs such as the liver, heart, and pancreas. 15,16 Liver data in cases of congenital heart disease (CHD) are particularly lacking, with only a few prior studies in children and adolescents with Fontan circulation that reported the potential value of the liver native T 1 values as a screening tool; 17,18 however, there is no data for adults with Fontan circulation. Furthermore, the correlations between the liver disease biomarkers and T 1 values remain unknown.…”
Section: Introductionmentioning
confidence: 99%